2020
DOI: 10.1007/s10494-020-00211-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Flow Visualization of Slightly Underexpanded Microjets by Mach–Zehnder Interferometers

Abstract: The Mach–Zehnder interferometer with the finite fringe setting is applied for a shock-containing microjet issued from an axisymmetric convergent nozzle with an inner diameter of 1.0 mm at the exit. Experiments are performed at a nozzle pressure ratio of 3.0 to produce a slightly underexpanded sonic jet where the Reynolds number, based upon the diameter and flow properties at the nozzle exit, is $$4.45 \times 10^4$$ 4.45 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The pressure-based compressible RANS equations are numerically solved. The Menter's SST k-ω turbulence model is employed because Sugawara et al [11] [12] showed that the RANS simulations with this turbulence model for round shock-containing microjets are in good quantitative agreement with experimental density fields captured by the Mach-Zehnder interferometry. The NPR is held constant at 5.0 where p os and p b are 500 kPa and 100 kPa, respectively, and the plenum temperature T os upstream of the nozzle is specified at 300 K. The dry air is assumed to follow the perfect gas law with a constant specific heat ratio of γ = 1.4, and the coefficient of viscosity is calculated by using the Sutherland's formula.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure-based compressible RANS equations are numerically solved. The Menter's SST k-ω turbulence model is employed because Sugawara et al [11] [12] showed that the RANS simulations with this turbulence model for round shock-containing microjets are in good quantitative agreement with experimental density fields captured by the Mach-Zehnder interferometry. The NPR is held constant at 5.0 where p os and p b are 500 kPa and 100 kPa, respectively, and the plenum temperature T os upstream of the nozzle is specified at 300 K. The dry air is assumed to follow the perfect gas law with a constant specific heat ratio of γ = 1.4, and the coefficient of viscosity is calculated by using the Sutherland's formula.…”
Section: Methodsmentioning
confidence: 99%
“…The projections of the magnitude of the density gradient vector onto the zy and zx planes are shown in Figure 5(a) and Figure 5(b), respectively. These are sometimes called the bright field schlieren [12] [14] or the circular-cutoff schlieren, which corresponds to schlieren with a disc-shaped filter.…”
Section: Shock Dynamicsmentioning
confidence: 99%